Successful Treatment with Sofosbuvir of Fibrosing Cholestatic Hepatitis C after Liver Transplantation in an HIV–HCV-Coinfected Patient. Issue 3 (April 2015) - Borentain, Patrick; Colson, Philippe; Dhiver, Catherine; Gregoire, Emilie; Hardwigsen, Jean; Botta-Fridlund, Danielle; Garcia, Stéphane; Gerolami, René
Fibrosing cholestatic hepatitis is a severe form of post-liver transplantation HCV recurrence. Fibrosing cholestatic hepatitis is characterized by its early onset and severe prognosis in HIV-infected patients. We report the case of an HIV–HCV genotype-4 coinfected patient successfully treated with a combination of sofosbuvir and ribavirin. After 4 weeks of treatment we observed a resolution of HCV recurrence related symptoms associated with a normalization of liver biochemistry and dramatic decrease of HCV viral load. This case illustrates the efficiency and tolerance of a sofosbuvir-based anti-HCV interferon-free regimen in post-liver HCV recurrence. Because of the absence of drug interactions between sofosbuvir and antiretroviral treatment or calcineurin inhibitors, its administration in HIV–HCV-coinfected liver transplanted patients is very promising.